(untitled) (JURNAL ADMINISTRASI PUBLIK, 2019)
This research is titled the empowerment of farming communities through a joint farmer group (Gapoktan) program in the village of Adow, Pinolosian Sub-district, South Bolaang Mongong District. This type of research uses qualitative research, the research informants are Gapoktan 1 person, 1 person Gapoktan Chairperson, 15 Gapoktan Members, 1 Gapoktan Farmer 1 person, 1 Person Village apparatus, data collection techniques using Interview, Observation, Documentation. Data analysis techniques using qualitative descriptive analysis research, the focus of this study using the theory according to Totok and Poerwok. the results of this study are the programs implemented by the Adow Village Gapoktan that have supported farmers in their efforts to achieve a better life. The Adow Village Gapoktan program has also been running well, those who play an active role in the program are those farmers who need empowerment. Keywords : Community; Empowerment. Farmers.